Digitalization and satisfaction among Peruvian users towards their civil registration office - Vicente Luquillas, Yeralyn Patrick (2022)
Digitalization is a reality for everyone, including the government. As a consequence, more govern- ments around the globe started to digitize their services, looking for more user satisfaction. In the case of Peru, the civil registration service, called RENIEC, found its particular way to implement digital solutions for their services. Therefore, did those efforts have any effect on the users’ satisfac- tion? The current analysis using ordinary least squares and Shapley’s value evaluated the impact of digitalization on user satisfaction. After the necessary research, we found that the birth and divorce digital process positively affected user satisfaction, while divorce did not.